General Energy Decay of Solutions for a Wave Equation with Nonlocal Damping and Nonlinear Boundary Damping (Journal of Partial Differential Equations, 2020)
In this paper, we consider a nonlinear wave equation with nonlocal damping and nonlinear boundary damping. We prove a general energy decay property forsolutions in terms of coefficient of the frictional boundary damping by using of themultiplier technique from the idea of Martinez [1]. Our result extends and improvesthe result in the literature such as the work by Lourêdo, Ferreira de Araújo and Mirandain [2] in which only exponential energy decay is considered. Furthermore, weget also the energy decay for the equation with nonlocal damping only but withoutnonlinear boundary damping.